Intraoperative esmolol infusion reduces postoperative analgesic consumption and anaesthetic use during septorhinoplasty: a randomized trial - Celebi,Nalan (2014)
Background and objectives:Esmolol is known to have no analgesic activity and no anaesthetic properties; however, it could potentiate the reduction in anaesthetic requirements and reduce postoperative analgesic use. The objective of this study is to evaluate the effect of intravenous esmolol infusion on intraoperative and postoperative analgesic consumptions as well as its effect on depth of anaesthesia.Methods:This randomized-controlled double blind study was conducted in a tertiary care hospital between March and June 2010. Sixty patients undergoing septorhinoplasty were randomized into two groups. History of allergy to drugs used in the study, ischaemic heart disease, heart block, bronchial asthma, hepatic or renal dysfunction, obesity and a history of chronic use of analgesic or β-blockers were considered cause for exclusion from the study. Thirty patients received esmolol and remifentanil (esmolol group) and 30 patients received normal saline and remifentanil (control group) as an intravenous infusion during the procedure. Mean arterial pressure, heart rate, and bispectral index values were recorded every 10min. Total remifentanil consumption, visual analogue scale scores, time to first analgesia and total postoperative morphine consumption were recorded.Results:The total remifentanil consumption, visual analogue scale scores at 0, 20 and 60 min, total morphine consumption, time to first analgesia and the number of patients who needed an intravenous morphine were lower in the esmolol group.Conclusions:Intravenous infusion of esmolol reduced the intraoperative and postoperative analgesic consumption, reduced visual analogue scale scores in the early postoperative period and prolonged the time to first analgesia; however it did not influence the depth of anaesthesia.